USING SCRABBLE GAMES TO ENHANCE STUDENTS' ABILITY AT VOCABULARY - Harahap, Arfita Wahyuni; Daulay, Sholihatul Hamidah; Dewi, Utami (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
A good education results in acceptable learning outcomes. Teachers must be able to use all available resources in order for pupils to learn effectively through creative learning. The use of media relevant to the conditions and situations at school is one of the efforts to maximize learning at home. The difficulties of teachers in choosing appropriate media, particularly when teaching English words, is a concern. pupils continue to have inadequate vocabulary mastery; as a result, pupils' learning results require innovation and effort. Scramble is one of the media that can be employed. Scrabble games can help children learn language quickly. They must arrange the words on the game board using the letter tiles provided. The method utilized to conduct this analysis is a qualitative research method since it produces good data. According to the findings of this study, scrabble not only promotes enthusiasm and interest, but it also improves students' vocabulary in terms of spelling, pronunciation, and learning vocabulary, and it also helps significantly their speaking skills. Classes become more enjoyable, and such classes can inspire students to become more enthusiastic and confident in their ability to communicate in English.